A bridge between worlds: Embedding research in telepractice co‐design with disability community - Cloe Benz (Learning Health Systems)
Abstract Introduction Co‐production approaches are increasingly being advocated for as a way of addressing the research translatory gap while including patient and public involvement in development of services they access, and particularly in disability service provision. Embedded research (ER) is a method which integrates the researcher within the target organization to better facilitate both co‐production of research outputs and the reduction of the research translation gap. The aim of this reflection is to better understand the commonalities and differences between ER in a disability context to accounts published in academic literature. Method A review of embedded researcher literature was completed in combination with a personal reflection of lived experience as an embedded researcher within a disability support service organization. The reflective process included review of research journal entries and other records of lived experience (photographs, audio recordings, drawings) maintained throughout the period in the role of embedded researcher. A reflexive thematic analysis process was used. Results I reflect throughout the article upon five themes which highlight both the commonalities between my experiences and those of other embedded researchers as well as instances where they differed. The five themes include (1) A knowledge bridge, (2) Considerations of positionality, (3) Ethical complexity, (4) Anticipating change, and (5) Existing in the in‐between together. Conclusion Experiences of ER appear to transcend the discipline in which the research is being embedded, and while the lived experience in a disability host organization was invaluable in facilitating a successful co‐produced research project, significant avenues for improvement exist in terms of ethical frameworks, methodological guidance, and communities of support.